Fundamental networking in Java - Pitt, Esmond ([New York] : Springer, 2010)
"This book is an in-depth learning and teaching resource for the understanding and programming of TCP/IP networking in Java. It covers "everything you can do to a socket in Java" and explains when and why you might - or might not - want to do that. It is addressed both to professional programmers and college students in first or second year networking courses." "The book covers TCP and UDP using both blocking streams and non-blocking channels, and also SSL secure sockets in both blocking and non-blocking modes, unravelling the mysteries of the SSLEngine in the process. Particular attention is paid to the neglected topics of multi-homing and multicast. A unique chapter on client and server architectures uses a quantitative approach rather than the usual design-patterns approach, leading to architectures with predictable performance rather than just coding elegance."--BOOK JACKET.
Ch. 1. Introduction -- Ch. 2. Fundamentals of IP -- Ch. 3. Fundamentals of TCP -- Ch. 4. Scalable I/O -- Ch. 5. Scalable TCP -- Ch. 6. Firewalls -- Ch. 7. Secure sockets -- Ch. 8. Scalable secure sockets -- Ch. 9. Unicast UDP -- Ch. 10. Scalable UDP -- Ch. 11. Multicast UDP -- Ch. 12. Server and client models -- Ch. 13. Fallacies of networking -- App. A. TCP port states -- App. B. Platform dependencies.
Includes bibliographical references (p. 357-358) and indexes.
Keywords: Java (Computer program language); TCP/IP (Computer network protocol); Computer networks; Internet programming